Studies on Complex Arylhydrazones. Part-VI - Prasad, N.; Sahay, A.; Srivastava, A.K. (Asian Journal of Chemistry, 2010)
Cu(II) complexes with 2,3-dioxobutyramide-2-phenylhydrazone have been investigated by means of physico-chemical methods which include analytical, spectral (IR and electronic) and magnetic moment measurements. The results obtained from such measurements have led to the elucidation of their structures and revelation of the nature of M-L bonding present therein.